2010
DOI: 10.1051/0004-6361/200912889
|View full text |Cite
|
Sign up to set email alerts
|

Weak13CO in the Cloverleaf quasar: evidence for a young, early generation starburst

Abstract: Observations of 12 CO at high redshift indicate rapid metal enrichment in the nuclear regions of at least some galaxies in the early universe. However, the enrichment may be limited to nuclei that are synthesized by short-lived massive stars, excluding classical "secondary" nuclei like 13 C. Testing this idea, we used the IRAM Interferometer to tentatively detect the 13 CO J = 3 → 2 line at a level of 0.3 Jy km s −1 toward the Cloverleaf quasar at z = 2.5. This is the first observational evidence for 13 C at h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 51 publications
5
44
0
Order By: Relevance
“…The observed 12 CO/ 13 CO line ratio was 40 and exceeds that seen in Arp 220 but is similar to that of NGC 6240 (Greve et al 2009). Henkel et al (2010) surmise that the high line ratio may be caused by a real deficiency in 13 …”
Section: Radiative Transfer Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed 12 CO/ 13 CO line ratio was 40 and exceeds that seen in Arp 220 but is similar to that of NGC 6240 (Greve et al 2009). Henkel et al (2010) surmise that the high line ratio may be caused by a real deficiency in 13 …”
Section: Radiative Transfer Modeling Resultsmentioning
confidence: 99%
“…Wilson & Rood 1994). Casoli et al (1992) have suggested that the observed higher 12 CO/ 13 CO line ratios seen in U/LIRGs, than in our Galaxy are likely due to an under-abundance of 13 CO and/or an over-abundance of 12 CO. Casoli et al (1992) Henkel et al (2010) have observed 13 CO J = 3-2 in the Cloverleaf quasar and have compared it to the 12 CO J = 3-2. The observed 12 CO/ 13 CO line ratio was 40 and exceeds that seen in Arp 220 but is similar to that of NGC 6240 (Greve et al 2009).…”
Section: Radiative Transfer Modeling Resultsmentioning
confidence: 99%
“…Furthermore, isotopologue selective chemical effects such as selective photodissociation and isotope charge exchange reactions can lead to isotope fractionation. When coupled with real variations in the elemental isotope abundances, such as in accreted primordial gas or cosmic-ray-dominated star formation paradigms, can lead to large variations in the isotopologue abundance ratios from species to species and galaxy to galaxy (Henkel et al 2010(Henkel et al , 2014Papadopoulos 2010;Papadopoulos et al 2011;Ritchey et al 2011;Roueff et al 2015). We therefore explore the effects of assuming an incorrect abundance ratio on the recovered T k and n H 2 , using HCN.…”
Section: Assumed [Hcn]/[h 13 Cn]mentioning
confidence: 99%
“…Recently, it has been suggested by Papadopoulos et al (2011) that a high [ 12 C]/[ 13 C] ratio might be evidence for a cosmic ray dominated star formation paradigm, leading to a top heavy stellar initial mass function (IMF) and thereby an excess of massive, 12 C producing, stars. Typical values of [ 12 C]/[ 13 C] in the local universe are ∼25 in the central Milky Way, 68 in the Milky Way as a whole and up to ∼100 in local starbursts and 100  in high-redshift ULIRGs (Milam et al 2005;Henkel et al 2010Henkel et al , 2014. Typically, these ratios are measured using a combination of observations of CN, 13 CN, CO, 13 CO and C 18 O lines.…”
Section: Chemical Modeling and Isotopologue Ratiosmentioning
confidence: 99%